TYPES OF PRONOUNS IN ENGLISH - Sobirjonova Mukhlisa Sobirjonovna; Haitmurodova Muyassar Alisher qizi (Galaxy International Interdisciplinary Research Journal, 2023)
In grammar, the time period "pronoun" refers no longer totally to nouns but, on the other hand, also to adjectives, numbers, and additionally to terms. For example, the U pronunciation essentially is certainly masculine, and any of the great genders can exchange the name; it calls the man and any subject of the truth a sign. Words can component out which, simply a very such sign, words where, where, when, how—some factor related to the place, time, or persona of actions for the situation.